2014
DOI: 10.1074/jbc.m114.567008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the R-modules in Alginate C-5 Epimerases AlgE4 and AlgE6 from Azotobacter vinelandii

Abstract: Background: Alginate epimerases consist of catalytic and noncatalytic domains of yet unknown function. Results: The noncatalytic domains of AlgE4 and AlgE6 possess different alginate binding behavior despite highly similar structures. Conclusion: Noncatalytic subunits of AlgE6 and AlgE4 influence the product specificity of the catalytic domain. Significance: This work opens a new route to designing alginate epimerases producing tailored alginates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 58 publications
1
50
1
Order By: Relevance
“…AlyA3 contains an alginate lyase module homologous to AlyA1 and AlyA2 linked to three calcium-binding modules homologous to the R-modules of secreted mannuronan C-5 epimerases (See Mannuronan C-5 Epimerases). It has been shown that R-modules can bind to alginate, although the binding strength is dependent on the specific R-module as well as the structure of the alginate molecule ( Buchinger et al, 2014 ). The cysts of Azotobacter sp.…”
Section: Alginate Lyasesmentioning
confidence: 99%
See 3 more Smart Citations
“…AlyA3 contains an alginate lyase module homologous to AlyA1 and AlyA2 linked to three calcium-binding modules homologous to the R-modules of secreted mannuronan C-5 epimerases (See Mannuronan C-5 Epimerases). It has been shown that R-modules can bind to alginate, although the binding strength is dependent on the specific R-module as well as the structure of the alginate molecule ( Buchinger et al, 2014 ). The cysts of Azotobacter sp.…”
Section: Alginate Lyasesmentioning
confidence: 99%
“…The A-modules are sufficient for both epimerization and for determining the epimerization pattern ( Ertesvåg and Valla, 1999 ). The R-modules are needed for full activity ( Ertesvåg and Valla, 1999 ) and has been shown to participate in substrate binding ( Buchinger et al, 2014 ). At their N-terminal ends each R-module contain four to seven copies of a nine amino acid long motif known to be involved in binding of Ca 2+ ( Baumann et al, 1993 ; Figure 3 ).…”
Section: Mannuronan C-5 Epimerasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several alginate C5 epimerases e.g., ref. 22 , virginiamycin B lyase e.g., ref. 23 and eukaryotic CMLEs 9 have some structural homology to CylK 24 .…”
Section: Discussionmentioning
confidence: 99%